Workload–Stress Nexus in High-Risk Public Service Occupations: Evidence from Traffic Police Officers in Indonesia - Diena Juliana; Raziki Waldan; Xiaomei Han (Institut Agama Islam Negeri Pontianak, 2026)
This study aims to examine the relationship between workload and work-related stress among traffic police officers within a high-risk law enforcement context. The research adopts a quantitative approach with a correlational design, involving 52 respondents selected through purposive sampling. Data were collected using standardized questionnaires measuring workload and work-related stress, and analyzed using descriptive and inferential statistics, including Pearson correlation analysis. The findings reveal that both workload and work-related stress are predominantly at moderate levels, and a significant positive relationship exists between the two variables, with a correlation coefficient of 0.667. This indicates that higher workload is associated with increased levels of work-related stress among traffic police officers. The study is limited by its relatively small sample size and its focus on a single institutional setting, which may restrict the generalizability of the findings. Practically, the results highlight the importance of effective workload management strategies to mitigate stress levels and enhance both performance and well-being among law enforcement personnel. The originality of this study lies in its empirical contribution to the limited body of literature on occupational stress within traffic policing in developing country contexts, offering insights relevant for human resource management and organizational policy in high-risk public service sectors.